Potential Herb-Drug Interactions Among Elderly Nursing Home Residents in Romania - Hanna Sebesi; László István Bába; Melinda Kolcsár; Zsolt Gáll; Soma Dávid (International Journal of Medical Students)
BACKGROUND: Herbal supplements are widely used as complementary or alternative medicines, but their phytochemical effects on conventional drugs are often overlooked. Evidence shows that herb-drug interactions (HDIs) are significant in clinical pharmacology. However, the current use of herbal supplements and the prevalence of HDIs among elderly patients in nursing homes is not known.